Symptom Experiences and Symptom Management of Persons with Chronic Obstructive Pulmonary Disease in a Tertiary Hospital, Sichuan Province, the People’s Republic of China - Yu, Dan; Srirat, Chomphoonut; Tachaudomdach, Chiraporn (Nursing Journal CMU, 2024)
Chronic Obstructive Pulmonary Disease (COPD) patients experiencing various distressed symptoms may seek strategies to relieve or get rid of these symptoms. The purposes of this study were to explore the symptom experiences and symptom management strategies of persons with COPD. 303 participants were recruited from a tertiary hospital in Sichuan, the People’s Republic of China. Research questionnaires were composed of demographic information and a clinical information form; the Memorial Symptom Assessment Scale, Chinese version (MSAS-Ch); and the COPD Symptom Management Strategies Questionnaire developed by the researchers and validated by six experts with a mean item-content validity index (I-CVI) of .84. The reliability, calculated by product moment correlation coefficient, was .89 for the MSAS-Ch, and .97 for the COPD Symptom Management Strategies Question- naire. Descriptive statistics were used to analyze data. The results showed 32 symptom experiences. The top three by the average of frequency, severity and distress scores were shortness of breath, lack of energy, and cough (Mean = 3.96, 3.80, and 3.56, respectively). In terms of symptom management, most participants used pharmacological and non-pharmacological management strategies. These findings provide basic information for clinical nurses to assess symptoms in every dimension and promote appropriate symptom management for people with COPD in China.